Alat Pencacah Pakan Ternak Menggunakan Motor Universal - Faraditha Amelia; Waode Zulkaidah; Sahabuddin Hay; Feliks Eldad Larobu; Agustina Lolok; Abd.Kadir (Piston: Jurnal Teknologi, 2022)
Feed is one of the most important factors in ruminant maintenance efforts, the success and failure of livestock business is largely determined by the feed given. Grass must be provided by breeders as the main feed for livestock every day. Additional feed must also be given to increase nutrition so that livestock meat grows faster. Additional feed such as bran, ingredients, concentrates, cassava, tofu dregs and others. The farmer took the initiative to mix the grass with additional feed to save costs. Before mixing, the grass must be chopped (chopped) first, so that the mixing process is easy to do. Every day the farmer must provide sufficient amount of grass for animal feed ingredients. In an effort to provide ruminant feed, breeders need tools so that in the process of chopping the grass even though it is large and the time and energy spent is still efficient. Therefore, a grass chopper is needed by breeders. In general, the lawn chopper consists of a motor that functions as a driver, transmission system, casing, frame shaft, and chopper blade. Things that must be considered in the manufacture of this grass chopper is how to make a machine with a strong frame, sharp knife to cut several times, ergonomic, affordable and easy to get on the market.